2009
DOI: 10.1093/nar/gkp074
|View full text |Cite
|
Sign up to set email alerts
|

No-match ORESTES explored as tumor markers

Abstract: Sequencing technologies and new bioinformatics tools have led to the complete sequencing of various genomes. However, information regarding the human transcriptome and its annotation is yet to be completed. The Human Cancer Genome Project, using ORESTES (open reading frame EST sequences) methodology, contributed to this objective by generating data from about 1.2 million expressed sequence tags. Approximately 30% of these sequences did not align to ESTs in the public databases and were considered no-match ORES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
0
8
0
3
Order By: Relevance
“…Potential new splice variants were flagged, putative new genes were revealed, noncoding intronic RNAs were found, and markers for loss of heterozygosis or gene amplification were selected. Mello et al, using ORESTES data as sequence tags, found, by cDNA microarrary analyses, differentially expressed genes in prostate tissues and confirmed these data by real‐time PCR.…”
Section: Discussionmentioning
confidence: 82%
“…Potential new splice variants were flagged, putative new genes were revealed, noncoding intronic RNAs were found, and markers for loss of heterozygosis or gene amplification were selected. Mello et al, using ORESTES data as sequence tags, found, by cDNA microarrary analyses, differentially expressed genes in prostate tissues and confirmed these data by real‐time PCR.…”
Section: Discussionmentioning
confidence: 82%
“…32 The amplicons were extracted from 1% agarose gel and cloned using the InsTAclone kit (Fermentas Life Science , Hanover, MD, USA). For 225 genes, a cDNA clone that covered at least 80% of the respective hcrHMs was retrieved from our cDNA bank from the Human Cancer Genome Project.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction and amplification besides microarray experiments are detailed in the supplemental material (Supplemental data 2), performed as described (Mello et al, 2009;Maschietto et al, 2011). Microarray data were deposited with the Gene Expression Omnibus (GEO) under accession number GSE19112.…”
Section: Cdna Microarray Experimentsmentioning
confidence: 99%